HOWL JENKINS PENDRAGON’S AND SOPHIE HATTER’S MOTIVATION IN DIANA WYNNE JONES’ HOWL’S MOVING CASTLE - Bella Safitri, Kanaya; Andayani, Ambar (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
This study of The Analysis of Motivation on Howl Jenkins Pendragon and Sophie Hatter in Diana Wynne Jones Howl’s Moving Castle discusses about Sophie Hatter and Howl Jenkins Pendragon’s characters and motivation. The aim of the study is to explain the characters and motivation to keep moving forward even though they have many problems in their life. The researcher uses a psychological approach of Maslow's hierarchy of needs, this is a motivational theory in psychology comprising a five-tier model of human needs, to analyze the motivation of Howl and Sophie. The researcher also applies qualitative descriptive analysis as the method to analyze the characters and motivation of Howl Jenkins Pendragon and Sophie Hatter. From this study, the researcher finds Howl and Sophie characters and their motivation in life. The motivation of Howl Jenkins Pendragon are breaking the curse, finding his true love, taking care of people that he must help, and learning how to be a better version of him. The motivation of Sophie are Finding a way how to be a better version of herself, breaking the curse, taking care of everyone who needs it and helping Howl to face his problem. All of them include the analysis how much their motivation relate to Maslow Hierarchy Theory.